Quality and Evaluation of Information Systems in Institutional Organizations: Archives and Libraries - Mamma, Eleni (Access: An International Journal of Nepal Library Association, 2023)
The factors affecting the success and efficiency of information systems are always an important and critical aspect for the structure, proper operation, and improvement of the produced services and products of an organization for its end users-both for the internal ones (employees) and for the external ones (public). At the present, the need to create suitable parameters, assisting in evaluating and measuring the successful operation of an information system in an organization is constantly growing. The purpose of the specific thesis is, firstly, to introduce us to the environment of the organizations’ information systems, while also providing us with a complete and extended presentation of their operations, processes, infrastructures, and factors of success. Through Systems Theory, we shall examine the analysis and design for an information system, while identifying the quality parameters necessary for measuring its success. In addition, we shall employ the model for measuring quality for an information system called: “DeLone & McLean Information Systems success model”. We shall see what each parameter of the above model examines by investigating concepts such as system quality, information quality, user satisfaction, effect of quality onuses and organization. At the same time, we shall develop an application for evaluating the quality of an information system, the so-called: "Organizational Memory Information Systems Quality" which builds on the success model of DeLone & McLean. The main objective of this thesis is to reach into a fruitful discussion regarding quality in the operation, infrastructure, and provided services of institutional organizations. Moreover, we shall focus on the usefulness and importance of measuring factors regarding efficiency for an information system, as this procedure is used by modern Society of Information, in order to be transformed to Society of Knowledge.